PP.18.01: ASYMPTOMATIC ORGAN DAMAGE IN TREATED AND UNTREATED HYPERTENSIVES. (June 2015) - Wojciechowska, W.; Stolarz-Skrzypek, K.; Olszanecka, A.; Klima, L.; Gasowski, J.; Grodzicki, T.; Czarnecka, D.
Abstract : Objective: Well controlled blood pressure during antihypertensive treatment results in regression of target organ damage which potentially is associated with favorable outcome. The study was aimed to compare arterial stiffness and echocardiographically determined parameters in subjects from general population with treated and untreated hypertension. Design and method: We recruited 303 (mean age, 46.9 years; 55% women) members from randomly selected families. SpaceLab 90207 monitors were programmed to obtain BP readings every 15 min. during daytime and every 30 min. at night. Peripheral and central pulse pressure (pPP; cPP), augmentation index (pAI; cAI) and pulse wave velocity (PWV) were evaluated by means of an oscillometric sphygmomanometer and pulse wave analysis (SphygmoCor software). Relative wall thickness (RWT), left atrial (LA) diameter, ascending aorta (AO) diameter, and ratio of early and late diastolic peak of transmitral flow velocities (E/A) as well as ratio of transmitral doppler early filling velocity to tissue doppler early diastolic mitral annular velocity (E/Em) were assessed by echocardiography (VIVID 7). Results: In the study group, there were 140 normotensives (NT), 61 untreated hypertensives (UTHT), and 102 treated hypertensives (THT). Parameters of interest significantly differed between these groups (p < 0.05). In post-hoc analysis with Bonferroni correction, UTHT had significantly higher blood pressure and evaluated target organ damage parameters in comparison to normotensives participants. Despite higher (p < 0.05) office (141.6/95.7 vs 135.1/ 85.9 (mmHg) and 24-h blood pressure (127.5/79.5 vs 121.2/72.6 mmHg) in UTHT, THT had significantly higher pAI, cAI, cPP, PWV, E/Em, lower E/A and larger LA (p < 0.05) in comparison to UTHT group. These differences remained significant after adjustment for age and sex. Hypertensive participants did not differ in terms of pPP, AO, RWT, LVMI (p > 0.1). Conclusions: Antihypertensive treatment was not associated with less pronounced target organ damage. This may reflect inadequate blood pressure control or too late initiation of antihypertensive therapy which result in progression of arterial and left ventricular stiffening. This also emphasizes the need of early diagnosis of elevated BP and early introduction of appropriate therapy.